How will tomorrow's world be fed? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Feeding tomorrow's world (Sextant, 3) 1990, 805 pages, ISBN 92 3 102083 8, UKL34.00,